Screening of novel acidified solvents for maximal antimicrobial peptide extraction from zophobas morio fabricius - Mohta, Johan Ariff; Yusof, Faridah; Ali, Najala Mahmoud Hag (AENSI Publications, 2014)
A solvent screening study using four alcohols with decreasing polarity to select novel acidified extraction solvents for maximal antimicrobial peptide (AMPs) recovery from the whole body extracts of supermealworm Zophobas morio larvae was performed. 20 grams of final instar larvae were homogenized in four solvents at fixed concentration of 90% methanol, 90% ethanol, 90% isopropanol and 90% butanol; each acidified with trifluoroacetic acid (TFA). All samples were extracted at constant solid-solvent ratio (w/v), extraction time and temperature. The solvent extracts were tested on four bacteria in the antimicrobial susceptibility test to evaluate the inhibitory effects. Inhibition zones (mm) were recorded and the range of values was categorized as good, moderate, weak and very weak antibacterial activity. All extracts were found to exhibit significant inhibitory effects on the bacteria (p < 0.001). Isopropanol extract produced significantly (p < 0.05) the largest zone of inhibition in Staphylococcus aureus (10.67 ± 3.06 mm), Escherichia coli (8.67 ± 2.08 mm), Klebsiella pneumonia (8.00 ± 1.00 mm) and Pseudomonas aeroginosa (7.00 ± 2.65 mm) compared to other solvent extracts. The extract was considered a good antibacterial agent against S. aureus, E. coli, and K. pneumonia and as a moderate antibacterial agent against P. aeroginosa. S. aureus was shown to be the most susceptible to isopropanol extract followed by E. coli, K. pneumonia and P. aeroginosa. This finding has a significant implication to improve the extraction procedure over the use of conventional methanolic extraction for new AMP discovery from insect whole body extracts. It appears that acidified isopropanol extracted a maximum amount of AMPs compared to acidified methanol, hence, is selected as the best novel solvent in this study.